Contribution of organic acids to α-terpinene antioxidant activity - Quiroga, Patricia Raquel (2019)
DPPH[rad] scavenging activity and antioxidant activity in canola oil of α-terpinene, BHT (butylated hydroxytoluene) and acetic, malic and citric acids and their mixtures were determined to examine the synergistic effect on the antioxidant activity. The results demonstrated that α-terpinene and organic acids had low or any activity against DPPH[rad] and BHT showed an IC50 of 0.035 mM. When mixed with organic acids, α-terpinene increased its activity showing a synergistic effect. The mix of α-terpinene (1.58 mM) and citric acid (2.91 mM) showed the higher synergistic effect in DPPH[rad] (121.82). BHT scavenging activity was inhibited by organic acids. Although the DPPH[rad] scavenging activity was enhanced for α-terpinene and inhibited for BHT by organic acids, the antioxidant activity in canola oil was not. It indicated that the scavenging DPPH activity and antioxidant activity in canola oil of a compound or a mixture of compounds are not always positively correlated with each other.